2017
DOI: 10.1002/joe.21840
|View full text |Cite
|
Sign up to set email alerts
|

The role of personal and job resources in boosting nurses’ work engagement and performance

Abstract: 37(2):32-40.To explore the influence of personal and job resources on nurses' work engagement and job performance, researchers developed a conceptual framework comprising the role of personality traits, self-efficacy, job characteristics, supervisor and coworker support, participation in decision making, and job security. Their analysis suggests that work engagement mediates the relationship among personal resources (personality traits and self-efficacy), job resources (job characteristics, supervisor and co-w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 32 publications
3
34
0
2
Order By: Relevance
“…These trends are important in making the financial case for health care organizations to invest in programs such as MEPRA, particularly when coupled with systemic structures that dismantle the factors undermining well-being and nurse engagement. 14,68,69 Turnover Intentions MEPRA participants, specifically nurses with less than 10 years of experience who reported higher TI before the program, reported decreased TI after training. This result demonstrates that the curricular intervention was more useful in lowering TI among participants who had worked as nurses for less than 10 years and had higher TI at baseline than among participants who had worked as nurses for 10 or more years and already had lower TI at baseline.…”
Section: Work Engagementmentioning
confidence: 99%
“…These trends are important in making the financial case for health care organizations to invest in programs such as MEPRA, particularly when coupled with systemic structures that dismantle the factors undermining well-being and nurse engagement. 14,68,69 Turnover Intentions MEPRA participants, specifically nurses with less than 10 years of experience who reported higher TI before the program, reported decreased TI after training. This result demonstrates that the curricular intervention was more useful in lowering TI among participants who had worked as nurses for less than 10 years and had higher TI at baseline than among participants who had worked as nurses for 10 or more years and already had lower TI at baseline.…”
Section: Work Engagementmentioning
confidence: 99%
“…Empirical research identified an array of factors as the antecedents of employee engagement (Saks, 2019). Job characteristics, including task variety, autonomy, feedback, task significance (Shantz et al, 2013), perceived organizational support (Brunetto et al, 2013;Saks, 2006), organizational justice (Ghosh et al, 2014;Saks, 2006), internal branding, including communication, training, and reward, empowerment (Karatepe, 2013), teamwork (Brunetto et al, 2013), person-job fit (Biswas & Bhatnagar, 2013), and such other factors are observed to be positively related to employee engagement (Bhatti et al, 2018;Thakre & Mathew, 2020).…”
Section: Employee Engagementmentioning
confidence: 99%
“…The recent research in the health care field supported the idea that job performance is a multidimensional concept (Bhatti et al., 2018). Due to the complexity of job performance as a construct, various studies examined potential predictors of job performance in the health care field (Amarat et al., 2019; Bhatti et al., 2018). Among the studied variables, concerning job performance is structural empowerment (Jaffery & Farooq, 2015).…”
Section: Introductionmentioning
confidence: 98%
“…Considering nurses' role in providing efficient care, job performance is a central concept in nursing (Mohamed & Gaballah, 2018). Thus, scholars extensively studied job performance in the health care field, especially in nursing (Bhatti et al., 2018). The recent research in the health care field supported the idea that job performance is a multidimensional concept (Bhatti et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation